Pengaruh Lama Miling Terhadap Sifat Absorpsi Material Penyimpan Hidrogen MgH2 yang Dikatalisasi Dengan Fe (The Role of Milling Time on the Absorption Behaviour of MgH2 Catalyzed by Fe) - Mustanir Mustanir; Zulkarnain Jalil (Bulletin of Chemical Reaction Engineering & Catalysis, 2009)
Hidrida logam berbasis MgH2 dengan sisipan 1 wt% katalis Fe telah berhasil disintesis dengan teknik ball milling. Hasil proses miling selama 80 jam menunjukkan bahwa ukuran butir material telah membentuk struktur nanokristal. Hal ini ditunjukkan oleh profil difraksi sinar-X dimana terjadi pelebaran puncakpuncak difraksinya dengan meningkatnya waktu miling. Hasil uji absorpsi secara gravimetrik diketahui bahwa MgH2 berkatalis 1 wt% Fe mampu menyerap hydrogen sebesar 5,5 wt% dalam waktu ~20 menit pada temperatur 300 oC. Hasil ini sekaligus memperlihatkan bahwa sejumlah kecil katalis Fe bekerja secara baik dalam memperbaiki sifat absorpsi material penyimpan hydrogen berbasis Mg.(Metal hydrides are of great interest as hydrogen storage media especially for automotive application. Hydrides of magnesium and magnesium alloys are particularly attractive as they combine potentially high hydrogen storage capacities, 7.6 wt%. But, unfortunately, the sorption properties are poor. For example, conventional hydrogenation of magnesium requires prolonged treatment at temperatures of 300 oC and above. Here, we report the absorption properties of MgH2 catalyzed with a small amount of Fe element (1wt%) under argon atmosphere prepared by ball milling in 80 hours. As the results, it showed the influence of milling time on the absortion kinetics of material which could absorp hydrogen in amount 5.5 within 20 minutes at 300 oC. It is obvious that longer milling time and small amount of catalyst could improve the sorption properties of Mg-based hydrides).© 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)